Heterogeneity derived from 18F‐FDG PET/CT predicts immunotherapy outcome for metastatic triple‐negative breast cancer patients. (11th March 2022) - Xie, Yizhao; Liu, Cheng; Zhao, Yannan; Gong, Chengcheng; Li, Yi; Hu, Shihui; Song, Shaoli; Hu, Xichun; Yang, Zhongyi; Wang, Biyun
Abstract: Background: Recently, immunotherapy has been used to treat metastatic triple‐negative breast cancer (mTNBC). Basic research has indicated a relation between tumor heterogeneity and the immune response. Tumor heterogeneity derived from 18 F‐FDG PET/CT is a potential predictor of chemotherapy results; however, few studies have focused on immunotherapy. This study aims to develop a convenient and efficient measurement of tumor heterogeneity for the prediction of immunotherapy in mTNBC patients. Methods: We enrolled mTNBC patients who received immunotherapy (PD‐1/PD‐L1 antibody) plus chemotherapy as first‐line treatment and underwent 18 F‐FDG PET/CT scans before treatment. We defined a novel index representing tumor heterogeneity calculated from the standard uptake value (SUV) as IATH and IETH. Optimal cutoffs were determined using time‐dependent receiver operator characteristics (ROC) analysis. Results: A total of 32 patients were enrolled and analyzed in this trial. A significantly longer median PFS was observed in the low SUVmax group than in the high SUVmax group (9.4 vs. 5.8 months, HR = 0.3, 95% CI 0.1–0.9, p = 0.025). The median PFS of low‐IATH patients was significantly longer than that of high‐IATH patients (HR = 0.3, 95% CI 0.1–0.8, p = 0.022). Similarly, patients with low IETH had significantly longer PFS than patients with high IETH (9.4 vs. 4.9 months, HR = 0.3, 95% CI 0.1–0.7, p = 0.01). Multivariate analysis demonstrated IETH as an independent predictor of PFS. Conclusions: This study proposed a novel method to assess intratumor and intertumor heterogeneity among metastatic breast cancer patients and determined that baseline IETH derived from 18 F‐FDG PET/CT could represent a simple and promising predictor for first‐line immunotherapy among mTNBC patients. Abstract : This study proposed a novel method to assess the intratumor and intertumor heterogeneity among metastatic breast cancer patients and figured out that baseline IETH derived from 18 F‐FDG PET/CT could be a simple and promising predictor for first‐line immunotherapy among mTNBC patients.